Experiences of the Molecular Diagnosis of Fragile X Syndrome in Ecuador - Pozo-Palacios, Juan; Llamos-Paneque, Arianne; Rivas, Christian; Onofre, Emily; López-Cáceres, Andrea; Villareal, Jenniffer (Frontiers in Psychiatry, 2021)
Fragile X syndrome (FXS) is the most common cause of hereditary intellectual disability and the second most common cause of intellectual disability of genetic etiology. This complex neurodevelopmental disorder is caused by an alteration in the CGG trinucleotide expansion in fragile X mental retardation gene 1 (FMR1) leading to gene silencing and the subsequent loss of its product: fragile X mental retardation protein 1 (FMRP). Molecular diagnosis is based on polymerase chain reaction (PCR) screening followed by Southern blotting (SB) or Triplet primer-PCR (TP-PCR) to determine the number of CGG repeats in the FMR1 gene. We performed, for the first time, screening in 247 Ecuadorian male individuals with clinical criteria to discard FXS. Analysis was carried out by the Genetics Service of the Hospital de Especialidades No. 1 de las Fuerzas Armadas (HE-1), Ecuador. The analysis was performed using endpoint PCR for CGG fragment expansion analysis of the FMR1 gene. Twenty-two affected males were identified as potentially carrying the full mutation in FMR1 and thus diagnosed with FXS that is 8.1% of the sample studied. The average age at diagnosis of the positive cases was 13 years of age, with most cases from the geographical area of Pichincha (63.63%). We confirmed the familial nature of the disease in four cases. The range of CGG variation in the population was 12–43 and followed a modal distribution of 27 repeats. Our results were similar to those reported in the literature; however, since it was not possible to differentiate between premutation and mutation cases, we can only establish a molecular screening approach to identify an expanded CGG repeat, which makes it necessary to generate national strategies to optimize molecular tests and establish proper protocols for the diagnosis, management, and follow-up of patients, families, and communities at risk of presenting FXS.